Maintenance of the gold value of the fund's assets - Gold, Joseph (Washington, 1971)
The first edition of this pamphlet was published in 1965. Since then the Articles of Agreement of the International Monetary Fund have been amended. The second edition takes into account those modifi cations of the Articles that affect the subject matter of the pamphlet. The opinions expressed are those of the author, who is the General Counsel and Director of the Legal Department of the Fund, and not necessarily those of the Fund itself.
Keywords: Financial economics